Pengaruh Penggunaan Madu Kaliandra (Calliandra callothyrsus) Kombinasi Ekstrak Buah Stroberi (Fragaria x ananassa) Konsentrasi 100% sebagai Bahan Alternatif untuk Pemutihan Gigi Secara in Vitro - Yusrini Pasril; Beauty Adinda Lestariana (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2022)
Tooth discoloration can be overcome by doing bleaching treatment. Bleaching is an act of using chemicals that can whiten teeth using peroxide. The method that can be used is the home bleaching technique or in office bleaching. The use of teeth whitening agents can cause side effects, namely on the mucosa and sensitivity of the teeth so that natural teeth whitening ingredients are needed using calliandra honey and strawberries. The elegat acid and malic acid in strawberries will undergo oxidation where these two acids can bind to substances that can cause discoloration of the enamel. This type of research is an experimental laboratory in vitro. The sample in this study amounted to 32 samples of teeth. The first treatment was soaked in calliandra honey, a combination of strawberry fruit extract with a concentration of 100% and the second treatment group was soaked in distilled water. Immersion was carried out for 14 days with 3 hours of immersion in the morning and 3 hours at night. Taking the number of samples using the Frederer's formula. The results of this study saw the effect of significant color changes before and after immersion using Calliandra honey in combination with 100% concentration of strawberry fruit extract.